2018
DOI: 10.3390/soils2010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ionic Strength on Arsenate Adsorption at Aluminum Hydroxide–Water Interfaces

Abstract: Adsorption processes at mineral-water interfaces control the fate and transport of arsenic in soils and aquatic systems. Mechanistic and thermodynamic models to describe this phenomenon only consider inner-sphere complexes but recent observation of the simultaneous adsorption of inner-and outer-sphere arsenate on single crystal surfaces complicates this picture. In this study, we investigate the ionic strength-dependence of the macroscopic adsorption behavior and molecular-scale surface speciation of arsenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Besides the above differences, the EXAFS-derived CN Al and As–Al interatomic distances R Al showed no change with varying phosphate concentrations for all samples explored on each mineral under various experimental conditions (Figure , Table S3). All of the EXAFS results indicate that arsenate adsorption mechanisms on gibbsite and bayerite are similar to results in our prior studies, , and these observed differences are largely preserved during competitive adsorption with phosphate (Figure S6). Therefore, the EXAFS results suggest that the suppression of arsenate adsorption due to phosphate addition occurs because of uniform competition at all binding sites and that no additional arsenate species form.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Besides the above differences, the EXAFS-derived CN Al and As–Al interatomic distances R Al showed no change with varying phosphate concentrations for all samples explored on each mineral under various experimental conditions (Figure , Table S3). All of the EXAFS results indicate that arsenate adsorption mechanisms on gibbsite and bayerite are similar to results in our prior studies, , and these observed differences are largely preserved during competitive adsorption with phosphate (Figure S6). Therefore, the EXAFS results suggest that the suppression of arsenate adsorption due to phosphate addition occurs because of uniform competition at all binding sites and that no additional arsenate species form.…”
Section: Resultssupporting
confidence: 85%
“…Different experimental conditions, such as pH variation, arsenate coverage, the addition of different amounts of phosphate, and mineral adsorbents, did not produce any distinctive patterns in EXAFS spectra (Figure S6), indicating the similar arsenate adsorption mechanisms on all samples explored. Structural model fits of the EXAFS spectra for all samples result an interatomic distance of around 1.7 and 3.2 Å for the first As–O and second As–Al shells, respectively, consistent with the bidentate binuclear inner-sphere arsenate surface complexes, identified in most previous studies. ,,,, Ideally, if arsenate only forms bidentate binuclear inner-sphere surface complexes, the coordination number for the Al neighbors associated with this species (CN Al ) should be exactly 2. However, our EXAFS fitting results showed the CN Al is much smaller than 2 for both minerals regardless of pH and arsenate surface coverage (Table S3), indicating the presence of an additional type of arsenate surface species such as monodentate inner-sphere or outer-sphere complexes.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Mixed inner- and outer-sphere species have been observed on other Fe-oxide (e.g., ferrihydrite and goethite) and Al-oxide surfaces, suggesting that a similar kinetic behavior of sulfate surface species may also be relevant to these minerals. , Given the large contribution of Fe- and Al-oxide minerals to sulfate adsorption by soils, this work may better inform not only sulfate adsorption on these minerals but soils on the whole . Furthermore, the experimental framework established here may be relevant to adsorption kinetics of other oxyanions which may form coexisting surface species on soil mineral surfaces, such as selenate, chromate, and arsenate. ,,, This interpretation is particularly relevant to further development of oxyanion adsorption kinetic models which rely on molecular-level assumptions regarding reaction mechanisms that we show may be experimentally verified, despite parameterization with an experimental kinetic model.…”
Section: Discussionmentioning
confidence: 80%